Long‐term safety and efficacy of dutasteride in the treatment of male patients with androgenetic alopecia. Issue 9 (19th February 2016) - Tsunemi, Yuichiro; Irisawa, Ryokichi; Yoshiie, Hiromu; Brotherton, Betsy; Ito, Hisahiro; Tsuboi, Ryoji; Kawashima, Makoto; Manyak, Michael; ,
Abstract: Androgenetic alopecia is an androgen‐induced pattern of progressive hair loss, which occurs in genetically predisposed people. This study aimed to determine long‐term safety, tolerability and efficacy of dutasteride 0.5 mg, an inhibitor of 5‐α‐reductase, in Japanese male patients with androgenetic alopecia. This was a multicenter, open‐label, prospective outpatient study (clinicaltrials.gov NCT01831791, GSK identifier ARI114264) in which patients took dutasteride 0.5 mg p.o. once daily for 52 weeks. Primary end‐points included adverse event assessment, incidence of drug‐related adverse event and premature discontinuations. Secondary end‐points included hair growth, hair restoration and global improvement in hair. A total of 120 patients were enrolled, of whom 110 completed 52 weeks of treatment. Nasopharyngitis, erectile dysfunction and decreased libido were the most frequently reported adverse events and most adverse events were mild. Drug‐related adverse events were reported with an incidence of 17%, none of which led to study withdrawal. Hair growth (mean target area hair count at week 52), hair restoration (mean target area hair width at week 52) and global appearance of hair (mean of the median score at week 52) improved from baseline during the study. As a potential future treatment option for male androgenetic alopecia, dutasteride 0.5 mg exhibited long‐term safety, tolerability and efficacy within this study population.